2020
DOI: 10.3389/fonc.2020.01034
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-DANCR Interferes With miR-125b-5p/HK2 Axis to Desensitize Colon Cancer Cells to Cisplatin vis Activating Anaerobic Glycolysis

Abstract: Colon cancer is one of the most prevalent malignancies that lead to high occurrence of cancer-related deaths. Currently, chemotherapies and radiotherapies remain the primary treatments for advanced colon cancer. Despite the initial effectiveness, a fraction of colon cancer patients developed cisplatin resistance, resulting in therapeutic failure. The long non-coding RNA differentiation antagonizing non-coding RNA (DANCR) has been shown to be upregulated in multiple cancers, indicating an oncogenic role of DANC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 37 publications
1
34
1
Order By: Relevance
“…In the study carried out by Xiong et al (2021), they investigated the role of the lncRNA DANCR in promoting DOX resistance in CRC cells. Similar to what was reported by Shi et al [269], DANCR was overexpressed in CRC tissues and cell lines, and in resistant cells, but in cells treated with DOX instead of cisplatin as the study of Shi et al [269]. When DANCR was silenced DOX induced apoptosis increased, which resulted in decreased cell numbers in G0/G1 phase but elevated cell numbers in S and G2/M phases, while when DANCR was overexpressed, the growth of resistant cells was promoted [281].…”
Section: Apoptosis-related Pathwaysupporting
confidence: 91%
See 3 more Smart Citations
“…In the study carried out by Xiong et al (2021), they investigated the role of the lncRNA DANCR in promoting DOX resistance in CRC cells. Similar to what was reported by Shi et al [269], DANCR was overexpressed in CRC tissues and cell lines, and in resistant cells, but in cells treated with DOX instead of cisplatin as the study of Shi et al [269]. When DANCR was silenced DOX induced apoptosis increased, which resulted in decreased cell numbers in G0/G1 phase but elevated cell numbers in S and G2/M phases, while when DANCR was overexpressed, the growth of resistant cells was promoted [281].…”
Section: Apoptosis-related Pathwaysupporting
confidence: 91%
“…In addition, its overexpression desensitised the colon cells to cisplatin, while this was reversed when this lncRNA was silenced. Further analyses revealed that DANCR acted as a ceRNA, being able to bind to miR-125b-5p, with the correlation between the two being negative since miR-125b-5p was downregulated when DANCR was overexpressed [269]. Moreover, overexpression of miR-125b-5p enhanced the sensitivity of cisplatin resistant cells.…”
Section: Emtmentioning
confidence: 99%
See 2 more Smart Citations
“…MiRNAs are short non-coding RNAs with a length of about 22nt and can target various genes by pairing with the mRNAs at the post-transcriptional level[ 14 , 15 ]. MiR-125b-5p is a well-investigated tumor suppressor in multiple cancer models, including bladder cancer, laryngeal squamous cell carcinoma, and colon cancer[ 16 - 18 ]. Furthermore, it has been well-identified that circRNAs and miRNAs are involved in the chemotherapy resistance in GC[ 8 , 19 - 21 ].…”
Section: Introductionmentioning
confidence: 99%